Language and graffiti of exceptional individuals: pedagogical strategies in West Africa - Obiozor, Williams Emeka (African journal of criminology and justice studies, 2008)
This paper establishes the place of language and graffiti practiced by exceptional individuals in the interpretation of family values, the preservation of culture and traditional heritage of the Igbo community in Southeastern Nigeria. The paper also takes a cursory look at graffiti art and exceptionality in a time when the Igbo tradition and culture were highly respected, jealously guarded and deep-rooted in the heart and soul of its people. Graffiti creations by exceptional individuals transfer both oral and visual education to documented tradition; for societal knowledge and awareness, individual wisdom, expressions against repression, pride and recognition of Igbo language and art. Unfortunately, the post-Nigeria civil war, evangelical movements with their doctrines and practices, including the influence of western culture; the highly revered expressive medium of exceptional minds are fast disappearing from the Igbo environment.